Three thousand years of farming strategies in central Thailand. (August 2020) - d'Alpoim Guedes, Jade; Hanson, Sydney; Lertcharnrit, Thanik; Weiss, Andrew D.; Pigott, Vincent C.; Higham, Charles F.W.; Higham, Thomas F.G.; Weber, Steven A.
Abstract: Abstract : In prehistoric coastal and western-central Thailand, rice was the dominant cultivar. In eastern-central Thailand, however, the first known farmers cultivated millet. Using one of the largest collections of archaeobotanical material in Southeast Asia, this article examines how cropping systems were adapted as domesticates were introduced into eastern-central Thailand. The authors argue that millet reached the region first, to be progressively replaced by rice, possibly due to climatic pressures. But despite the increasing importance of rice, dryland, rain-fed cultivation persisted throughout ancient central Thailand, a result that contributes to refining understanding of the development of farming in Southeast Asia.